Voxel-Based Imaging of Translocator Protein 18Kda (TSPO) in High-Resolution PET. Issue 3 (March 2013) - Ko, Ji Hyun; Koshimori, Yuko; Mizrahi, Romina; Rusjan, Pablo; Wilson, Alan A; Lang, Anthony E; Houle, Sylvain; Strafella, Antonio P
In vivo imaging of translocator protein 18 kDa (TSPO) has received significant attention as potential biomarker of microglia activation. Several radioligands have been designed with improved properties. Our group recently developed an 18 F-labeled TSPO ligand, [ 18 F]-FEPPA, and confirmed its reliability with a 2-tissue compartment model. Here, we extended, in a group of healthy subjects, its suitability for use in voxel-based analysis with the newly proposed graphical analysis approach, Relative-Equilibrium-Gjedde-Patlak (REGP) plot. The REGP plot successfully replicated the total distribution volumes estimated by the 2-tissue compartment model. We also showed its proof-of-concept in a patient with possible meningioma showing increased [ 18 F]-FEPPA total distribution volume.